Characteristics of low-rank and medium-rank Indonesian coal using the TG-DSC method. Issue 1 (November 2021) - Hariana,; Prismantoko, A; Putra, H P; Nuryadi, A P; Sugiarto,; Enjang,; Nielsen, C
Abstract: Low-rank and medium-rank coal are dominant coal resources in Indonesia. Considering the decisive role of coal in coal-fired power plants, it is crucial to examine the combustion characteristics before burning coal in the boiler. This paper presents the effect of moisture content, heating value, and volatile matter on ignition temperature and burn out of five samples of low-rank coal and five samples of medium-rank coal using TG-DSC analysis which was carried out using LINSEIS High-Pressure STA at atmospheric pressure with an air rate of 25 ml/min and heating rate of 10 °C/min. The investigation results show that low-rank coal with the higher volatile matter has tremendous reactivity and is more flammable, and favours of burning through itself than medium-rank coal. Medium-rank coal has better combustion with short residence time because it has a lower burnout temperature (Tbo ) value than low-rank coal. However, medium-rank coal burns more instantly because it has a lower temperature interval than low-rank coal. Medium-rank coal, which has fixed carbon and higher heating value, but lower moisture content, has a higher Rmax value than low-rank coal. In conjunction with these properties, it is crucial to examine the implementation in boilers.